Usage and constraints of urban river corridors at Hutuo River, Shijiazhuang, China - Shi, Lin (2024)
This PhD thesis investigates the utilization and associated constraints of urban river corridors in inland Chinese cities, focusing on Shijiazhuang. Recently, local authorities have increasingly recognized the importance of the Hutuo River Corridor and have sought to balance its ecological needs with socioeconomic development, aiming for sustainable revitalization and effective urban space use. However, planning and design processes often overlook user needs and expectations, particularly the variations in usage across different social demographics. To address these gaps, this study comprises three components: systematic literature review, survey, and thematic and textual analysis using social media data. The systematic review identified 59 relevant studies from 27 journals, leading to the proposal of a social-ecological framework that emphasizes the roles of individual, social, physical, and timerelated factors in shaping urban river corridor utilization. A survey of 620 respondents, using both on-site and online semi-structured questionnaires, revealed that social demographics—such as gender, age, marital status, education level, income, and residential proximity—significantly influence river corridor usage. Key constraints identified include accessibility issues (traffic congestion, crowding, inadequate facilities, and unavailable toilet services) and external factors like seasonality and weather. In the era of big data, social networks provide diverse data that facilitate investigating dynamic aspects of human activities and environmental factors. An analysis of 3,006 comments from Dianping revealed positive evaluations of the natural environment, planning, design, convenience facilities, and transportation, but also dissatisfaction with certain charged events. This study proposes a conceptual framework that advances the understanding of urban river corridor utilization and constraints by integrating social-ecological perspectives and employing a mixed-methods approach. The findings underscore the need for a peopleoriented approach in urban planning by identifying user patterns and key constraints across diverse social demographics, offering practical insights for enhancing river corridor environments. The study provides actionable recommendations for urban planners and decision-makers to improve the management and design of river corridors in Shijiazhuang and similar urban settings.